C3 gas phase selective hydrogenation reaction and obtained hydrogenation reaction product

By using a support with oxygen-containing groups on the surface and performing appropriate surface treatment, the problem of unstable catalyst performance in the prior art is solved, and a carbon three-gas phase selective hydrogenation catalyst with high activity, high selectivity and stable performance is achieved.

CN119707624AActive Publication Date: 2025-03-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311261103.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28
Estimated Expiration
2043-09-27

AI Technical Summary

Technical Problem

The existing carbon three-gas phase selective hydrogenation catalyst and its preparation method are easily affected by fluctuations in the physical properties of alumina support, resulting in unstable catalyst performance.

Method used

The support with oxygen-containing groups on the surface is used, and the number of oxygen-containing groups on the surface is increased by heat treatment, crystallization, oxidation and other surface treatment methods, so that the metal active components are distributed more uniformly, and a catalyst with excellent catalytic activity and high selectivity is prepared.

Benefits of technology

The stability and consistency of catalyst performance are achieved, catalytic activity and selectivity are improved, the amount of green oil is reduced, and the operation cycle of the catalyst is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004475291200000111
    Figure BDA0004475291200000111
  • Figure BDA0004475291200000112
    Figure BDA0004475291200000112
Patent Text Reader

Abstract

The invention provides a C3 gas phase selective hydrogenation reaction and an obtained hydrogenation reaction product. The C3 gas-phase selective hydrogenation reaction provided by the invention comprises a step of carrying out contact reaction on a C3 gas-phase fraction and a catalyst, the catalyst comprises a carrier, a main active metal component loaded on the carrier and an optionally added auxiliary active metal component, and the density of oxygen-containing groups on the surface of the carrier is 0.1-6 mmol / m < 2 >. The oxygen-containing groups on the surface of the carrier promote the uniform distribution of the metal active components, so that the catalyst has high activity and selectivity in the C3 gas phase selective hydrogenation reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a C3 gas-phase selective hydrogenation reaction and an obtained hydrogenation reaction product. Background Art

[0002] In the device for producing ethylene and propylene by steam thermal cracking, the separated C3 fraction usually contains 1 mol% to 6 mol% of propyne (MA) and propadiene (PD), which are often collectively referred to as MAPD. The propylene obtained after distillation of the C3 fraction contains trace amounts of MAPD, which will increase the consumption of polypropylene catalyst and reduce the performance of polypropylene products, so it needs to be removed. In industry, the method of selective hydrogenation is generally used to convert propyne and propadiene into propylene, which can both remove impurities and increase propylene production. There are two ways to remove propyne and propadiene: gas phase hydrogenation process and liquid phase hydrogenation process. The former has the advantages of good MAPD removal effect and low MAPD content at the reactor outlet; the latter has the advantages of reasonable energy utilization, low green oil production, and long operation cycle.

[0003] The C3 gas phase selective hydrogenation catalyst generally uses palladium as the main active component, silver is added as an additive, and alumina is used as a carrier. In order to inhibit the formation of green oil, extend the catalyst operation cycle, and further improve the activity and selectivity, the catalyst is often modified by adding other metal additives, using new alumina carriers, and optimizing the catalyst preparation process. Chinese patent CN1279126A discloses the use of diatomaceous earth, SiO2, TiO2, Al2O3, etc. as carriers, and the use of Bi additives to modify Pd catalysts, which have high selectivity in the selective hydrogenation reaction of alkynes, reduce the amount of green oil generated, and extend the catalyst operation cycle. Chinese patent CN1958155A discloses an alkyne selective hydrogenation catalyst coated with Al2O3 coating on talcum powder, refractory clay or silicon carbide inert carriers, using Pd as the main active component, Ag, alkali metals, etc. as auxiliary active components, and by controlling the thickness of the alumina coating, the distribution of metal active components on the carrier surface is promoted, thereby improving activity and selectivity.

[0004] The existing C3 gas phase selective hydrogenation catalyst and its preparation method are easily affected by the fluctuation of the physical properties of the alumina carrier. The catalyst performance prepared by the alumina carrier produced in different batches is different. Therefore, it is necessary to develop a C3 gas phase selective hydrogenation catalyst with a simple preparation method, stable mass production performance, good activity and selectivity. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a C3 gas-phase selective hydrogenation reaction. The catalyst used in the hydrogenation reaction comprises a carrier, and a main active metal component and an auxiliary active metal component loaded on the carrier. The surface of the carrier is rich in oxygen-containing groups, and the metal active components loaded on the surface are more uniform, so that the catalyst exhibits excellent catalytic activity, and the C3 gas-phase selective hydrogenation reaction has higher selectivity.

[0006] One of the purposes of the present invention is to provide a C3 gas phase selective hydrogenation reaction, comprising the step of contacting a C3 gas phase fraction with a catalyst for reaction, wherein the catalyst comprises a carrier, a main active metal component supported on the carrier and an optionally added auxiliary active metal component, and the surface oxygen-containing group density of the carrier is 0.1 to 6 mmol / m 2 .

[0007] According to the present invention, in the C3 gas phase selective hydrogenation reaction:

[0008] The surface oxygen-containing group density of the carrier is 0.1 to 4 mmol / m 2 ;

[0009] In the carrier, the surface oxygen-containing groups are at least two of hydroxyl groups, carboxyl groups, and lactone groups. Preferably, the content of the hydroxyl groups is 2 to 40 mmol / g, the content of the carboxyl groups is 2 to 40 mmol / g, and the content of the lactone groups is 1 to 30 mmol / g;

[0010] The specific surface area of ​​the carrier is 40 to 200 m 2 / g, water absorption rate is 30-120%, strength is 30-150N / grain, bulk density is 0.4-1.0g / ml, pore volume is 0.3-1.2ml / g;

[0011] Other oxides other than aluminum oxide are optionally added to the carrier. Preferably, the other oxides are selected from at least one of titanium oxide, barium oxide, magnesium oxide, calcium oxide and silicon oxide.

[0012] According to the present invention, in the C3 gas phase selective hydrogenation reaction:

[0013] The main active metal component is Pd; in terms of mass percentage, the content of the main active metal component in the catalyst is 0.02-0.2%, preferably 0.02-0.15%;

[0014] The auxiliary active metal component is selected from at least one of Ag, Bi, Zn and Ga; in terms of mass percentage, the content of the auxiliary active metal component in the catalyst is 0 to 0.2%;

[0015] The contents of Pd and the auxiliary active metal components can be measured by atomic absorption or ICP methods. Those skilled in the art can select a specific test method according to the type and content of the metal.

[0016] According to the present invention, in the C3 gas phase selective hydrogenation reaction:

[0017] The catalyst is subjected to reduction treatment before use. Preferably, the gas used for reduction includes hydrogen and other gases, the other gas is nitrogen or methane, and the molar percentage of hydrogen in the gas is 10-90%; the reduction temperature is 90-350° C., and the reduction time is 2-24 hours;

[0018] In the C3 gas phase fraction, the total molar percentage of propyne and propadiene is 0.5-6%;

[0019] The conditions of the hydrogenation reaction are: reaction temperature is 30-150°C, reaction space velocity is 500-6000h -1 .

[0020] According to the present invention, in the C3 gas phase selective hydrogenation reaction, the catalyst is obtained by the following preparation process: a solution containing a main active metal compound and an optionally added auxiliary active metal compound is loaded onto a carrier, and the catalyst is obtained after drying and calcining.

[0021] According to the present invention, during the preparation process of the catalyst:

[0022] The main active metal compound is selected from at least one of soluble palladium compounds, preferably at least one of palladium chloride, palladium nitrate, palladium acetate and palladium sulfate;

[0023] The auxiliary active metal compound is selected from at least one of chlorides, nitrates, acetates, sulfates, oxides, and metal organic compounds of Ag, Bi, Zn, and Ga, preferably at least one of chlorides, nitrates, and acetates of Ag, Bi, Zn, and Ga;

[0024] The solvent in the solution is selected from at least one of water, hydrochloric acid, nitric acid, acetic acid, and alcohol, preferably water;

[0025] The metal concentration in the solution containing the metal compound can be adjusted within a wide range, for example, the total content of the metal elements in the solution is 0.01 to 350 mg / mL;

[0026] The loading method can adopt the loading method commonly used in the art, for example, the metal components can be loaded on the carrier together, or different metal components can be loaded on the carrier step by step;

[0027] The drying process can adopt the drying process and drying conditions commonly used in the art. The drying process allows the solvent used for impregnation to fully volatilize. The time required for drying can be selected according to the amount of solvent used and the drying temperature. For example, the drying conditions are: the drying temperature is 50 to 250° C. and the drying time is 2 to 36 hours; preferably, the drying temperature is 50 to 200° C. and the drying time is 4 to 24 hours;

[0028] The calcination can adopt the calcination process and calcination conditions commonly used in the art. The calcination time varies according to the content of the metal active component. As the content of the metal active component increases, the calcination time can be appropriately increased. For example, the calcination conditions are: the calcination temperature is 250-850°C, and the calcination time is 2-36h.

[0029] According to the present invention, the carrier and its preparation can refer to patent ZL202311028071.8, and the relevant contents disclosed in the aforementioned document are introduced into the present invention as a reference. Specifically, the carrier is obtained by the following preparation process: components including alumina powder, a molding agent, a pore-forming agent, an inorganic carbon species, and optionally other oxides other than alumina are mixed to obtain a mixed material, and then an acidic solution is added to knead and shape, extruded into granules, dried, and surface treated to obtain the carrier.

[0030] According to the present invention, during the preparation of the carrier:

[0031] The alumina powder can be any alumina-containing powder material in the prior art. For example, the alumina powder is selected from at least one of pseudo-boehmite powder, alumina trihydrate powder, fast-release alumina powder, and γ-Al2O3 powder. The pseudo-boehmite powder can be commonly used pseudo-boehmite. Preferably, the specific surface area of ​​the pseudo-boehmite powder is 200-300 m 2 / g, pore volume 0.5-1.2ml / g, bulk density 0.2-0.4g / ml; the alumina trihydrate powder can be selected from at least one of gibbsite, bayerite, and diaspore; the fast-dehydrating alumina powder is obtained by fast dehydration of aluminum hydroxide, wherein the mass content of Na and Fe is less than 0.1%; the γ-Al2O3 powder can be obtained by high-temperature calcination of commonly used pseudo-boehmite powder;

[0032] The molding agent is selected from at least one of polyethylene glycol cellulose, methyl cellulose, carboxymethyl cellulose, sodium hydroxymethyl cellulose, hydroxypropyl methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose and starch; the amount of the molding agent is 0.05-8wt% of the total weight of the mixture;

[0033] The pore-forming agent is selected from at least one of polyvinyl alcohol, polyethylene glycol, polyacrylamide, polypropylene glycol, and sesbania powder; the amount of the pore-forming agent is 0.05-10wt% of the total weight of the mixed material;

[0034] The inorganic carbon species is selected from at least one of coke, activated carbon, carbon black, glassy carbon, charcoal, bamboo charcoal, coconut shell charcoal, graphene, graphyne, and diamond; the amount of the inorganic carbon species is 0.1 to 12 wt% of the total weight of the mixed material;

[0035] The other oxides except aluminum oxide are selected from at least one of titanium oxide, barium oxide, magnesium oxide, calcium oxide and silicon oxide; the amount of the other oxides except aluminum oxide is 0 to 20 wt% of the total weight of the mixed material;

[0036] The concentration of the acidic solution can be adjusted within a wide range. Preferably, the concentration of the acidic solution is 0.01 to 0.5 mol / L.

[0037] The solvent in the acidic solution is selected from water or a mixed solution of water and an organic solvent. Preferably, the organic solvent is selected from at least one of methanol, ethanol, and ethylene glycol. When the solvent in the acidic solution is a mixed solution of water and an organic solvent, the dosage ratio of the organic solvent to water can be adjusted within a wide range, for example, the volume ratio of the organic solvent to water is (0.01-1):1.

[0038] The acidic compound in the acidic solution is selected from at least one of organic acids and inorganic acids, preferably at least one of acetic acid, maleic acid, malic acid, citric acid, oxalic acid, formic acid, tartaric acid, ascorbic acid, salicylic acid, succinic acid, nitric acid, sulfuric acid, hydrochloric acid, hypochlorous acid, and phosphoric acid.

[0039] In the preparation method of the carrier, those skilled in the art can adjust the amount of acid in the acidic aqueous solution according to the required carrier specific surface area, strength, bulk density and other data; the kneading molding and extrusion granulation steps, the kneading molding time, and the extrusion molding pressure are related to factors such as the size of the equipment used, the composition of the alumina powder, and the composition of the acid solution, and those skilled in the art can determine them specifically based on experience.

[0040] According to the present invention, during the preparation of the carrier:

[0041] The drying process is not particularly limited, and the drying equipment and drying conditions in the prior art can be used. For example, the drying conditions are drying at 60 to 180° C. for 4 to 24 hours;

[0042] The surface treatment is selected from at least one of heat treatment, crystallization, oxidation, alkalization, and irradiation treatment; preferably,

[0043] The heat treatment conditions include: the heat treatment atmosphere includes a first atmosphere and a second atmosphere, the first atmosphere is selected from at least one of carbon dioxide, water vapor, acetylene, ethylene, and methane, the second atmosphere is selected from at least one of air, nitrogen, argon, and helium, the volume ratio of the first atmosphere to the second atmosphere is (0.05-1):1, the heat treatment temperature is 300-1200°C, the heat treatment time is 1-24h, and the pressure is 0.1-3MPa;

[0044] The crystallization conditions are: temperature of 120-250° C., pressure of 0.2-15 MPa, time of 4-18 h, and the solvent used for crystallization is at least one selected from water, ethanol, ethylene glycol, and ethylenediamine;

[0045] The oxidation conditions are: temperature of 30-110° C., time of 0.2-10 h, the oxidant used for oxidation is at least one selected from nitric acid, sulfuric acid, ammonium persulfate, hydrogen peroxide, potassium permanganate, and ascorbic acid, and the concentration of the oxidant solution is 0.1-10 mol / L;

[0046] The alkalization conditions are as follows: the temperature is 30-110°C, the time is 0.2-10h, the alkaline compound used for alkalization is selected from at least one of sodium hydroxide, sodium bicarbonate, sodium carbonate, sodium acetate, sodium oxalate, sodium citrate, potassium hydroxide, potassium bicarbonate, potassium carbonate, potassium acetate, and potassium citrate, and the concentration of the alkaline compound solution is 0.1-10 mol / L;

[0047] The conditions for the irradiation treatment are: the ray source is selected from gamma rays and / or microwaves, wherein the gamma ray irradiation dose rate is 2-90 kGy / min, and the irradiation time is 0.2-24 h; the microwave power is 50-1000 W, and the irradiation time is 0.5-60 min.

[0048] According to the present invention, during the preparation of the carrier:

[0049] When the inorganic carbon species is at least one of coke, activated carbon, carbon black, and glassy carbon, heat treatment is used, or surface treatment is performed by crystallization and oxidation;

[0050] When the inorganic carbon species is at least one of charcoal, bamboo charcoal, and coconut shell charcoal, heat treatment is used, or heat treatment and irradiation are used for surface treatment;

[0051] When the inorganic carbon species is at least one of graphene, graphyne and diamond, the surface treatment is carried out by crystallization and oxidation, or by heat treatment and alkalization, or by heat treatment, alkalization and irradiation.

[0052] The second object of the present invention is to provide a hydrogenation reaction product obtained by the above-mentioned C3 gas phase selective hydrogenation reaction. Preferably, in the hydrogenation reaction product, the total molar percentage of propyne and propadiene is less than 1000 μmol / mol.

[0053] The C3 gas-phase hydrogenation catalyst provided by the present invention adopts a carrier with a surface rich in oxygen-containing groups, and a molding precursor such as pseudo-boehmite powder, alumina trihydrate powder, etc. and an inorganic carbon species are kneaded into a mold, and then surface treated to increase the number of surface oxygen-containing groups to obtain a carrier; then Pd metal components and auxiliary active metal components are loaded on the carrier, and high-temperature roasting is performed after drying to obtain a catalyst. The present invention uses heat treatment, crystallization, oxidation, irradiation treatment and other means in the process of carrier preparation to increase the number of oxygen-containing groups on the carrier surface, so that the loaded metal active components are more evenly distributed, and the catalyst exhibits better activity and selectivity. In addition, the surface of alumina is modified after molding, and the physical properties of different batches of carriers are more consistent, the industrial production repeatability is better, and the performance of the prepared C3 gas-phase hydrogenation catalyst is also more stable. DETAILED DESCRIPTION

[0054] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0055] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0056] Example 1

[0057] Carrier preparation: Take 100g pseudo-boehmite powder (specific surface area 201.5m 2 / g, pore volume 0.83ml / g, bulk density 0.24g / ml), 6g sesbania powder, 6g carboxymethyl cellulose, and 6g coconut shell carbon are uniformly mixed; 2.10g concentrated sulfuric acid is added into 140g deionized water to prepare an acid solution; the acid solution is added into the uniformly mixed powder for kneading, and then extruded to obtain cylindrical particles with a particle size of 2-4mm; dried at 110℃ for 4h; then heat treated with air and water vapor (volume ratio 0.5:1) at 1200℃, 0.2MPa for 12h to obtain a carrier.

[0058] Active metal component loading method: Take 10 mL of 10 mg Pd / mL palladium nitrate solution, weigh 0.158 g silver nitrate and add it to the palladium nitrate solution, dilute it to 65 mL with deionized water, and impregnate it on 100 g of the carrier prepared by the above method. The impregnated sample was dried at 120°C for 4 hours and calcined at 500°C for 4 hours to obtain catalyst S1, with a Pd loading of 0.10% and an Ag loading of 0.10% by mass.

[0059] Example 2

[0060] Preparation of carrier: Take 100g of pseudo-boehmite powder, 2g of starch, 3g of methyl cellulose, and 10g of bamboo charcoal powder the same as in Example 1 and mix them evenly; take 1.50g of concentrated nitric acid and add it to 120g of deionized water to prepare an acid solution; add the acid solution to the mixed powder and knead it, then extrude it to obtain cylindrical particles with a particle size of 2-4mm; dry it at 90°C for 12h; then heat treat it with 280°C, 2MPa carbon dioxide and nitrogen (volume ratio 1:1) for 1h, then soak it in 3mol / L potassium carbonate solution, soak it at 65°C for 2h, and then irradiate it with 2kGy / min of gamma rays for 6 hours to obtain a carrier.

[0061] Active metal component loading method: Take 10 mL of 10 mg Pd / mL palladium chloride solution, dilute to 58 mL with deionized water, impregnate on 100 g of the carrier prepared by the above method, dry at 120 ° C for 4 hours, and calcine at 450 ° C for 6 hours to obtain a Pd-containing catalyst precursor. Weigh 0.895 g of zinc nitrate, add it to 58 ml of deionized water, stir evenly and impregnate the Pd-containing catalyst precursor, then dry at 120 ° C for 4 hours, and calcine at 450 ° C for 6 hours to obtain catalyst S2, which has a Pd loading of 0.10% and a Zn loading of 0.20% by mass content.

[0062] Example 3

[0063] Carrier preparation: Take 90g of alumina trihydrate powder (specific surface area 150.3m 2 / g, pore volume 1.22ml / g, bulk density 0.16g / ml), 15g titanium oxide, 6g polyethylene glycol, 7g methyl cellulose, 12g graphene, mix well; take 6g acetic acid, add it into 140g deionized water, prepare it into an acid solution; add the acid solution into the mixed powder and knead it, then extrude it to obtain cylindrical particles with a particle size of 2-4mm; crystallize it at 250℃ and 12MPa for 4h (the crystallization solvent is water), then soak it in a mixed solution of 5mol / L hydrogen peroxide and 5mol / L potassium permanganate at 30℃ for 0.5h, and freeze-dry it at -20℃ for 4h to obtain a carrier.

[0064] Active metal component loading method: Take 12mL of 10mg Pd / mL palladium nitrate solution, dilute it to 71mL with deionized water, add 0.158g silver nitrate thereto, stir evenly and impregnate it on 100g of the carrier prepared by the above method, dry it at 120℃ for 12h, and calcine it at 480℃ for 4hr to obtain a catalyst precursor containing Pd and Ag; take 0.4ml of bismuth nitrate solution containing 50mgBi / ml, dilute it to 71ml with deionized water, impregnate the catalyst precursor containing Pd and Ag, then dry it at 120℃ for 8h, and calcine it at 500℃ for 8h to obtain catalyst S3, which has a Pd loading amount of 0.12%, an Ag loading amount of 0.10%, and a Bi loading amount of 0.02% by mass content.

[0065] Example 4

[0066] Preparation of carrier: Take 100g pseudo-boehmite powder (physical properties are the same as those in Example 1), 10g α-Al2O3 powder, 10g γ-Al2O3 powder, 6g sesbania powder, 6g starch, and 5g carbon black and mix them evenly; take 2.0g concentrated nitric acid and 2.0g acetic acid, add them to 150g deionized water to prepare a mixed acid solution; add the acid solution to the mixed powder and knead it, then extrude it to obtain cylindrical particles with a particle size of 2-4mm; dry it at 120℃ for 4h; crystallize it at 120℃ and 0.2MPa for 18h (the crystallization solvent is water), then soak it in a mixed solution of 0.1mol / L nitric acid and 0.1mol / L hydrogen peroxide at 80℃ for 8h, and freeze-dry it at -20℃ for 8h to obtain a carrier.

[0067] Active metal component loading method: Take 5 mL of 10 mg Pd / mL palladium nitrate solution, dilute it to 65 mL with deionized water, add 0.158 g silver nitrate thereto, stir evenly and then impregnate it on 100 g of the carrier prepared by the above method, dry it at 120°C for 8 h, and calcine it at 450°C for 6 h to obtain catalyst S4. By mass content, the Pd loading amount is 0.05% and the Ag loading amount is 0.10%.

[0068] Example 5

[0069] Preparation of carrier: Take 100g pseudo-boehmite powder (physical properties are the same as in Example 1), 20g alumina trihydrate powder (physical properties are the same as in Example 3), 10g barium oxide powder, 5g polyethylene glycol cellulose, 8g polyvinyl alcohol, and 20g diamond powder and mix them evenly; take 7.0g ascorbic acid and 3.1g acetic acid, add 180g ethanol and deionized water (volume ratio 1:10) solution to prepare a mixed acid solution; add the acid solution to the mixed powder and knead, then extrude and shape to obtain cylindrical particles with a particle size of 2-4mm; dry at 100°C for 4h; heat treat at 320°C, 0.3MPa acetylene and argon (volume ratio 0.05:1) atmosphere for 5h, soak in 0.1mol / L sodium hydroxide solution, soak at 35°C for 5h, and then irradiate with 50W microwave for 60min to obtain a carrier.

[0070] Active metal component loading method: 15 mL of 10 mg Pd / mL palladium chloride solution was taken, diluted to 70 mL with deionized water, and impregnated onto 100 g of the carrier prepared by the above method, dried at 110°C for 12 h, and calcined at 450°C for 8 h to obtain a Pd-containing catalyst precursor. 0.743 g of gallium nitrate was weighed, added to 70 ml of deionized water, impregnated with the Pd-containing catalyst precursor, then dried at 120°C for 12 h, and calcined at 500°C for 12 h to obtain catalyst S5, with a Pd loading of 0.15% and a Ga loading of 0.20% by mass.

[0071] Comparative Example 1

[0072] Preparation of the carrier: Take 100g of pseudo-boehmite powder (physical properties are the same as those in Example 1), 5g of sesbania powder, and 8g of carboxymethyl cellulose, and mix them evenly; take 1.80g of concentrated nitric acid, add it to 150g of deionized water, and prepare a mixed acid solution; add the acid solution to the evenly mixed powder and knead it, then extrude it to obtain cylindrical particles with a particle size of 2-4mm; dry it at 110°C for 4h; then heat treat it with air at 1200°C and 0.2MPa for 12h to obtain the carrier.

[0073] Active metal component loading method: 16 mL of 10 mg Pd / mL palladium nitrate solution was taken, diluted to 65 mL with deionized water, and impregnated onto 100 g of the carrier prepared by the above method. After drying at 120°C for 12 h and calcining at 500°C for 8 h, catalyst D1 was obtained. The Pd loading amount was 0.16% by mass content.

[0074] Comparative Example 2

[0075] Preparation of carrier: Take 100g of pseudo-boehmite powder (physical properties are the same as those in Example 1), 2g of starch, 3g of methyl cellulose, and 10g of bamboo charcoal powder and mix them evenly; take 1.50g of concentrated nitric acid and add it to 120g of deionized water to prepare an acid solution; add the acid solution to the mixed powder and knead it, then extrude it to obtain cylindrical particles with a particle size of 2-4mm; then heat treat it with air at 1185°C and 0.2MPa for 12h to obtain a carrier.

[0076] The active metal component loading method was the same as that of Comparative Example 1 to obtain catalyst D2.

[0077] Comparative Example 3

[0078] Preparation of the carrier: Take 100g of pseudo-boehmite powder (physical properties are the same as those in Example 1), 10g of α-Al2O3 powder, 10g of γ-Al2O3 powder, 6g of sesbania powder, and 6g of starch; take 2.0g of concentrated nitric acid and 2.0g of acetic acid, add them to 150g of deionized water to prepare a mixed acid solution; add the acid solution to the uniformly mixed powder and knead it, then extrude it to obtain cylindrical particles with a particle size of 2-4mm; dry it at 120°C for 4h; crystallize it at 120°C and 0.2MPa for 18h (the crystallization solvent is water), then soak it in a mixed solution of 0.1mol / L nitric acid and 0.1mol / L hydrogen peroxide at 80°C for 8h, and freeze-dry it at -20°C for 8h to obtain the carrier.

[0079] The active metal component loading method was the same as that of Comparative Example 1 to obtain catalyst D3.

[0080] Test Case

[0081] Determination method of oxygen-containing groups on the carrier: The Boehm chemical method was used to determine the nature and quantity of oxygen-containing groups on the carrier. Weigh three portions of 0.6g of the carrier and soak them in 40ml of 0.05mol / L NaHCO3, Na2CO3 and NaOH solutions for 24h. 10ml of the soaking solution was titrated with 0.05mol / L hydrochloric acid. Each sample was titrated three times, and the arithmetic mean was taken. The number of various oxygen-containing groups on the carrier was calculated based on the consumption of alkali, and the oxygen-containing group density was obtained in combination with the carrier specific surface data. The results are listed in Table 1.

[0082] Table 1. Test results of oxygen-containing groups of carriers in Examples and Comparative Examples

[0083]

[0084] It can be seen from Table 1 that the content and density of oxygen-containing groups on the surface of the carrier prepared by the method of the present invention are significantly higher than those of the carrier of the comparative example. By adjusting the raw material ratio, preparation process parameters and conditions, the method of the present invention can achieve the regulation of the number and type of oxygen-containing groups on the surface of the carrier.

[0085] Test Case

[0086] The above catalyst was used to carry out gas phase selective hydrogenation of C3, and the experimental conditions were as follows:

[0087] Take 10ml of catalyst and load it into a stainless steel tubular reactor. After nitrogen replacement, introduce hydrogen to reduce at 160℃ for 2hr; after cooling to room temperature, purge with nitrogen; then introduce C3 gas phase reaction material. The general molar composition of the reaction material is: 3.25% propane, 0.85% propadiene, 1.25% propyne, propylene as balance gas, the molar ratio of hydrogen to MAPD is 1.0-2.5, and the reactor inlet temperature is 52℃. Under the same reaction conditions, the MAPD content and propylene selectivity at the reactor outlet of each catalyst were investigated.

[0088] The calculation method of propylene selectivity (%) is:

[0089]

[0090] In the formula, MAPD stands for propyne and propadiene, (MAPD) in is the content of MAPD at the reactor inlet, (MAPD) out is the content of MAPD at the reactor outlet, (C2H6) in is the content of C2H6 at the reactor inlet, (C2H6) out is the content of C2H6 at the reactor outlet, and the contents of the above components are measured by a gas chromatograph equipped with a FID detector.

[0091] Table 2. Catalyst evaluation results obtained in Examples and Comparative Examples

[0092] catalyst MAPD content (μmol / mol) Selectivity (%) S1 3 61.3 S2 5 55.2 S3 3 65.5 S4 2 61.4 S5 1 61.5 D1 19 41.3 D2 22 40.7 D3 15 47.9

[0093] It can be seen from the results in Tables 1 to 2 that, compared with Comparative Examples 1 to 3, in Examples 1 to 5, by adding carbon-containing components and different surface treatment methods, the content of oxygen-containing groups on the surface of the carrier can be regulated and prepared, the catalytic activity of the catalyst can be improved, and the catalyst is used in the gas-phase selective hydrogenation reaction of C3. The MAPD (propyne and propadiene) content at the reactor outlet of Examples 1 to 5 is significantly lower than that of the Comparative Examples, and the selectivity is also higher.

Claims

1. A C3 gas phase selective hydrogenation reaction, comprising the step of contacting a C3 gas phase fraction with a catalyst for reaction, wherein the catalyst comprises a carrier, a main active metal component supported on the carrier and an optionally added auxiliary active metal component, and the surface oxygen-containing group density of the carrier is 0.1 to 6 mmol / m 2 .

2. The C3 gas phase selective hydrogenation reaction according to claim 1, characterized in that: The surface oxygen-containing group density of the carrier is 0.1 to 4 mmol / m 2 and / or, In the carrier, the surface oxygen-containing groups are at least two of hydroxyl, carboxyl and lactone groups. Preferably, the content of the hydroxyl group is 2 to 40 mmol / g; and / or, the content of the carboxyl group is 2 to 40 mmol / g; and / or, the content of the lactone group is 1 to 30 mmol / g; and / or, The specific surface area of ​​the carrier is 40 to 200 m 2 / g, water absorption rate of 30-120%, strength of 30-150N / grain, bulk density of 0.4-1.0g / ml, pore volume of 0.3-1.2ml / g; and / or, Other oxides other than aluminum oxide are optionally added to the carrier. Preferably, the other oxides are selected from at least one of titanium oxide, barium oxide, magnesium oxide, calcium oxide and silicon oxide.

3. The C3 gas phase selective hydrogenation reaction according to claim 1, characterized in that: The main active metal component is Pd; and / or, In terms of mass percentage, the content of the main active metal component in the catalyst is 0.02-0.2%, preferably 0.02-0.15%; and / or, The auxiliary active metal component is selected from at least one of Ag, Bi, Zn and Ga; and / or, Calculated by mass percentage, the content of the active metal component in the catalyst is 0-0.2%.

4. The C3 gas phase selective hydrogenation reaction according to claim 1, characterized in that: The catalyst is subjected to reduction treatment before use. Preferably, the gas used for reduction includes hydrogen and other gases, the other gas is nitrogen or methane, and the molar percentage of hydrogen in the gas is 10-90%; and / or, the reduction temperature is 90-350° C.; and / or, the reduction time is 2-24 hours; and / or, In the C3 gas phase fraction, the total molar percentage of propyne and propadiene is 0.5-6%; and / or, The conditions of the hydrogenation reaction are: the reaction temperature is 30-150°C, and / or the reaction space velocity is 500-6000h -1 .

5. The C3 gas phase selective hydrogenation reaction according to claim 1, characterized in that: The catalyst is obtained by the following preparation process: a solution containing a main active metal compound and an optionally added auxiliary active metal compound is loaded onto a carrier, and the catalyst is obtained after drying and calcining.

6. The C3 gas phase selective hydrogenation reaction according to claim 5, characterized in that: The main active metal compound is selected from at least one of soluble palladium compounds, preferably at least one of palladium chloride, palladium nitrate, palladium acetate and palladium sulfate; and / or, The auxiliary active metal compound is selected from at least one of chlorides, nitrates, acetates, sulfates, oxides and metal organic compounds of Ag, Bi, Zn and Ga, preferably at least one of chlorides, nitrates and acetates of Ag, Bi, Zn and Ga; and / or, The solvent in the solution is selected from at least one of water, hydrochloric acid, nitric acid, acetic acid and alcohol, preferably water; and / or, In the solution, the total content of metal elements is 0.01 to 350 mg / mL; and / or, The drying conditions are: drying temperature of 50-250°C, drying time of 2-36h; preferably, drying temperature of 50-200°C, drying time of 4-24h; and / or, The calcination conditions are as follows: the calcination temperature is 250-850° C. and the calcination time is 2-36 hours.

7. The C3 gas phase selective hydrogenation reaction according to claim 5, characterized in that: The carrier is prepared by the following process: mixing components including alumina powder, a molding agent, a pore-forming agent, an inorganic carbon species, and optionally other oxides other than alumina to obtain a mixed material, then adding an acidic solution for kneading and molding, extruding and granulating, drying, and surface treatment to obtain the carrier.

8. The C3 gas phase selective hydrogenation reaction according to claim 7, characterized in that: The alumina powder is selected from at least one of pseudo-boehmite powder, alumina trihydrate powder, fast-release alumina powder, and γ-Al2O3 powder; and / or, The molding agent is selected from at least one of polyethylene glycol cellulose, methyl cellulose, carboxymethyl cellulose, sodium hydroxymethyl cellulose, hydroxypropyl methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose and starch; and / or, The amount of the molding agent is 0.05-8wt% of the total weight of the mixture; and / or, The pore-forming agent is selected from at least one of polyvinyl alcohol, polyethylene glycol, polyacrylamide, polypropylene glycol and sesbania powder; and / or, The amount of the pore-forming agent is 0.05-10 wt% of the total weight of the mixture; and / or, The inorganic carbon species is selected from at least one of coke, activated carbon, carbon black, glassy carbon, charcoal, bamboo charcoal, coconut shell charcoal, graphene, graphyne, and diamond; and / or, The amount of the inorganic carbon species is 0.1 to 12 wt% of the total weight of the mixture; and / or, The other oxides except aluminum oxide are selected from at least one of titanium oxide, barium oxide, magnesium oxide, calcium oxide and silicon oxide; and / or, The amount of the other oxides except aluminum oxide is 0 to 20 wt% of the total weight of the mixed material; and / or, The concentration of the acidic solution is 0.01-0.5 mol / L; and / or, The solvent in the acidic solution is selected from water or a mixed solution of water and an organic solvent. Preferably, the organic solvent is selected from at least one of methanol, ethanol and ethylene glycol. And / or, when the solvent in the acidic solution is a mixed solution of water and an organic solvent, the volume ratio of the organic solvent to water is (0.01-1):1; and / or, The acidic compound in the acidic solution is selected from at least one of organic acids and inorganic acids, preferably at least one of acetic acid, maleic acid, malic acid, citric acid, oxalic acid, formic acid, tartaric acid, ascorbic acid, salicylic acid, succinic acid, nitric acid, sulfuric acid, hydrochloric acid, hypochlorous acid, and phosphoric acid.

9. The C3 gas phase selective hydrogenation reaction according to claim 7, characterized in that: During the preparation of the carrier: The drying condition is 60-180° C. for 4-24 hours; and / or, The surface treatment is selected from at least one of heat treatment, crystallization, oxidation, alkalization, and irradiation treatment; preferably, The heat treatment conditions include: the heat treatment atmosphere includes a first atmosphere and a second atmosphere, the first atmosphere is selected from at least one of carbon dioxide, water vapor, acetylene, ethylene, and methane, the second atmosphere is selected from at least one of air, nitrogen, argon, and helium, the volume ratio of the first atmosphere to the second atmosphere is (0.05-1):1, the heat treatment temperature is 300-1200°C, the heat treatment time is 1-24h, and the pressure is 0.1-3MPa; and / or, The crystallization conditions are: temperature of 120-250° C., pressure of 0.2-15 MPa, time of 4-18 h, and the solvent used for crystallization is at least one selected from water, ethanol, ethylene glycol, and ethylenediamine; and / or, The oxidation conditions are: temperature of 30-110° C., time of 0.2-10 h, the oxidant used for oxidation is at least one selected from nitric acid, sulfuric acid, ammonium persulfate, hydrogen peroxide, potassium permanganate, and ascorbic acid, and the concentration of the oxidant solution is 0.1-10 mol / L; and / or, The alkalization conditions are as follows: the temperature is 30-110° C., the time is 0.2-10 h, the alkaline compound used for alkalization is selected from at least one of sodium hydroxide, sodium bicarbonate, sodium carbonate, sodium acetate, sodium oxalate, sodium citrate, potassium hydroxide, potassium bicarbonate, potassium carbonate, potassium acetate, and potassium citrate, and the concentration of the alkaline compound solution is 0.1-10 mol / L; and / or, The conditions for the irradiation treatment are: the ray source is selected from gamma rays and / or microwaves, wherein the gamma ray irradiation dose rate is 2-90 kGy / min, and the irradiation time is 0.2-24 h; and / or the microwave power is 50-1000 W, and the irradiation time is 0.5-60 min.

10. The C3 gas phase selective hydrogenation reaction according to claim 9, characterized in that: When the inorganic carbon species is at least one of coke, activated carbon, carbon black, and glassy carbon, heat treatment is used, or surface treatment is performed by crystallization and oxidation; or, When the inorganic carbon species is at least one of charcoal, bamboo charcoal, and coconut shell charcoal, heat treatment is used, or heat treatment and irradiation are used for surface treatment; or, When the inorganic carbon species is at least one of graphene, graphyne and diamond, the surface treatment is carried out by crystallization and oxidation, or by heat treatment and alkalization, or by heat treatment, alkalization and irradiation.

11. A hydrogenation reaction product obtained by the gas phase selective hydrogenation reaction of C3 as claimed in any one of claims 1 to 10.

Citation Information

Patent Citations

  • Alumina carrier as well as preparation method and application thereof

    CN119500087A

  • Catalyst for selective hydrogenation of acetylene hydrocarbon

    CN1279126A

  • Selective hydrogenation catalyst of alkine and diolefin, preparation method and application

    CN1958155A

  • Carbon 3 fraction selective hydrogenation reaction method

    CN103864559A

  • Catalyst for selective hydrogenation of C3 and preparation method thereof, and hydrogenation method

    CN107970949A